Cross-Species and Cross-Polymorph Seeding of Lysozyme Amyloid Reveals a Dominant Polymorph - Rahimi Araghi, Lida; Dee, Derek R. (Frontiers in Molecular Biosciences, 2020)
The ability to self-propagate is one of the most intriguing characteristics of amyloid fibrils, and is a feature of great interest both to stopping unwanted pathological amyloid, and for engineering functional amyloid as a useful nanomaterial. The sequence and structural tolerances for amyloid seeding are not well understood, particularly concerning the propagation of distinct fibril morphologies (polymorphs) across species. This study examined the seeding and cross-seeding reactions between two unique fibril polymorphs, one long and flexible (formed at pH 2) and the other short and rigid (formed at pH 6.3), of human lysozyme and hen egg-white lysozyme. Both polymorphs could cross-seed aggregation across species, but this reaction was markedly reduced under physiological conditions. For both species, the pH 6.3 fibril polymorph was dominant, seeding fibril growth with a faster growth rate constant at pH 2 than the pH 2 polymorph. Based on fibrillation kinetics and fibril morphology, we found that the pH 2 polymorph was not able to faithfully replicate itself at pH 6.3. These results show that two distinct amyloid polymorphs are both capable of heterologous seeding across two species (human and hen) of lysozyme, but that the pH 6.3 polymorph is favoured, regardless of the species, likely due to a lower energy barrier, or faster configurational diffusion, to accessing this particular misfolded form. These findings contribute to our better understanding of amyloid strain propagation across species barriers.